Overview of recent and upcoming activities at the BATMAN Upgrade test facility. Issue 1 (1st April 2022) - Wimmer, C.; Briefi, S.; Fröschle, M.; Heinemann, B.; den Harder, N.; Hurlbatt, A.; Mimo, A.; Nocentini, R.; Orozco, G.; Fantz, U.
Abstract: The BATMAN Upgrade (BUG) test facility at IPP is contributing to the development of RF-driven H - sources towards the ITER neutral beam injection and beyond. BUG is equipped with an 1/8 size of the ITER NBI ion source and thus is highly flexible for setup changes or diagnostic access. The present strategy for BUG is aligned along two paths: (i) BUG is continuing to be upgraded upgrading for long pulse operation (up to 1 hour, both in H and D) to identify measures for the stabilization of long pulses. For pulses > 100 s a cooling of the plasma grid (first grid of the extraction system) is required in order to avoid the dominance of thermal Cs desorption. A Cs evaporation concept with evaporation close to the extraction system is being tested, showing a stabilization of co-extracted electrons in 100 s H pulses, (ii) BUG is used for investigations of whole beam and beamlet optics for which the beam diagnostics have been massively upgraded. The beam diagnostics have been used to characterize a newly installed MITICA-like extraction system including asymmetric deflection compensation magnets.